Morphological characteristics and isozyme banding patterns of Cucurbita moschata at different altitudes - NUR RAHMAH HIDAYATI; SURANTO SURANTO; SAJIDAN SAJIDAN (Society for Indonesian Biodiversity, 2018)
Hidayati NR, Suranto, Sajidan. 2018. Morphological characteristics and isozyme banding patterns of Cucurbita moschata at different altitudes. Biodiversitas 19: 1683-1689. Aims of this research were to investigate the morphological character and isozyme banding patterns of Cucurbita moschata plants grown at three different altitudes. Samples in this study consisted of leaf, stem, and flowers. The morphological characters were conducted by direct observation in the field and analyzed descriptively as well as statically by one way ANOVA. The isozyme bands appearance of esterase and peroxidase of leaf samples were conducted using polyacrylamide gel electrophoresis (PAGE). Qualitative approach was used to analyze the presence and the absence of isozyme bands, while Retardation factor (Rf) was used to analyze quantitatively. The results showed that most plants grown at middle altitude (351-750 m asl.) were well-developed in terms of length of leaves, stems and flowers. Accordingly, the isozyme banding pattern of peroxidase was also found varied in plants grown at middle altitudes from which the presence of very unique bands was detected. Conversely, the band detected in plants grown at the lower and the highest altitudes was similar in term of band's number but it was different in the quality of the bands. Meanwhile, esterase isozyme banding pattern of plants grown at the lower and higher altitude had more bands than the middle altitude. Based on this result it is obvious that the isozyme data could be used to support in understanding the diversity morphological characters of plants grown in three different altitudes. This early result suggests that altitudes as a crucial factor in contributing the expression of isozyme appearance, which is useful for further pumpkin characterizations.